The Management of Very Small/Blister Internal Carotid Artery Aneurysms - Le Feuvre, D.E.J. (Centauro S.r.l., 2011)
Blood blister aneuryms are uncommon lesions that have a poor natural history. Because there is no clear aneurysmal sac to treat they remain challenging lesions to manage whether the approach is endovascular or surgical. Although the management of intracranial cerebral aneurysms has changed subsequent to the results published by the ISAT trial, there still exist groups of aneurysms which do not lend themselves to endovascular management. There are recent reports of successful endovascular management using flow diverting approaches but experience is limited and relying on flow change may be insufficient to prevent re-rupture. Surgery when possible offers the advantage of immediate vessel wall reconstruction.